Working Poverty in Metro Vancouver - Ivanova, Iglika (Canadian Centre for Policy Alternatives, BC Office, 2016)
This study examines Metro Vancouver working poverty trends by neighbourhood pre- and post- the 2008 recession. We are often told that the solution to poverty is for the poor to “get a job” or for various sectors to create more jobs. But this study finds that a job is not a guaranteed path out of poverty. Over 100,000 working-age people in Metro Vancouver were working but stuck below the poverty line in 2012, not counting students and young adults living at home with their parents. Contrary to stereotypes about poverty being concentrated mainly in Vancouver and Surrey, this study finds the growing ranks of the working poor are spread out across the Metro Vancouver region. The study explores the economic and public policy contributing to working poverty and develops recommendations for change. The study is a co-publication of the Canadian Centre for Policy Alternatives – BC Office, the United Way of the Lower Mainland, and the BC Poverty Reduction Coalition.